Comparações entre doses pediátricas periféricas provenientes de radioterapia conformal e de intensidade modulada - Santos, Marinei do Rocio Pacheco dos (2010)
This research presents and compares peripheral pediatric doses measurements in radiation therapy, for of thyroid, heart, breast, abdomen, ovaries and testicles regions, obtained with TLD LiF: Mg, Ti (TLD-100) powder, placed on three humanoid phantoms with sizes of children as two, five and ten years old, made of high density polyethylene and completely filled with water. It at linear accelerator Varian Clinac 600CD was employed to irradiate the heads of the three phantoms, with X-rays beams generated by a potential of 6 MV, with three different skull plannings: (a) IMRT sliding window with multileaf collimator rotated 0°, (b) IMRT sliding window with the multileaf collimator rotated 90° and (c) conformal planning (3D). The doses applied were 300 cGy and 600 cGy with five coplanar fields for all cares planning. The results show that the doses obtained for the all irradiations are very low compared to deterministic dose values deterministic for the regions of greater interest in radiological protection and that IMRT 90º provides more shielding for leakage radiation which would be directed to patient's body, offering advantages when compared to conformal planning and IMRT 0º.